CAN TECHNOLOGY-ENHANCED FLIPPED LEARNING INSTILL CHARACTER EDUCATION? INDONESIAN UNDERGRADUATE EFL STUDENTS’ PERCEPTIONS - Triarisanti, Risa; Lubis, Arif Husein; Ansas, Velayeti Nurfitriana (University of Kuningan, 2022)
The advantages of incorporating technology-enhanced flipped learning in English classrooms are nothing new. However, the impact of incorporating the learning method on the occurrence and decline of students’ characters has not much been revealed. This study aims to fill the void by exploring the students’ perceptions of whether flipped learning and the use of technology in learning English can instill character education. Eighty-four (n=84) Indonesian undergraduate EFL students participated in this study. A 22-item questionnaire with a checklist and open-ended types was filled out after the students completed a 16-week course. While percentages were obtained from the checklist responses, codes and categories were generated from the open-ended responses. The results revealed that flipped learning could instill character values of responsibility, independence, and curiosity. The in-class group discussion was considered as the most contributing activity to the instillment of character values. Character values of religiosity, patriotism, and nationalism were less occurred among the students. Furthermore, the use of ICT-based learning media such as YouTube, WhatsApp, the Internet, and mobile phone could instill character values of independence, creativity, teamwork, activeness, and criticality. However, few students perceived that such learning media could influence them to commit cheating or become less concentrated during group discussion. This study emphasizes the teacher’s roles in designing learning activities oriented to developing the students’ English language skills and character.